Penalty ADM Algorithm for Cardinality Constrained Mean-Absolute Deviation Portfolio Optimization - Temadher AlMaadeed; Tahereh Khodamoradi; Maziar Salahi; Abdelouahed Hamdi (Statistics, Optimization & Information Computing, 2022)
In this paper, we study the cardinality constrained mean-absolute deviation portfolio optimization problem with risk-neutral interest rate and short-selling. We enhance the model by adding extra constraints to avoid investing in those stocks without short-selling positions. Also, we further enhance the model by determining the short rebate based on the return. The penalty alternating direction method is used to solve the mixed integer linear model. Finally, numerical experiments are provided to compare all models in terms of Sharpe ratios and CPU times using the data set of the NASDAQ and S&P indexes.